The effect of financial development towards poverty rate in Malaysia / Nurul Fasihah Zahid - Zahid, Nurul Fasihah (2017)
The aim of this research is to determine the financial development factors that affect poverty rate in Malaysia. The period of this study is from 1986 to 2015 which are 30 years. The research used secondary data and it is a time series research. The dependent variable is poverty rate while the independent variable is financial development. The proxy for poverty rate is household final consumption expenditure per capita while the financial development factors consist of domestic credit to private sector, broad money, inflation and trade. All of the data are obtained from World Bank Databank and the data are regressed using EViews8 software using Ordinary Least Square (OLS) method. Based on the regressed output, only broad money, inflation and trade are significant with poverty rate while domestic credit to private sector is insignificant with poverty rate. Domestic credit to private sector and inflation have positive relationship with poverty rate, while broad money and trade have negative relationship with poverty rate. Based on the assumption test conducted, the error term is normally distributed, exist serial correlation of error term, no multicollinearity between variables, the error term is homoscedasticity and no specification error of error term.